Directed organization of gold nanoclusters on silver nanowires: a step forward in heterostructure assembly - Sharma, J.; Vivek, J. P.; Vijayamohanan, K. P.; Singh, P.; Dharmadhikari, C. V. (Applied Physics Letters, 2006)
We investigate the directed assembly of tridecylamine protected gold nanoclusters of 4-5 nm size on functionalized silver nanowires of 55-60 nm diameter and the electron transfer behavior of this integrated structure using transmission electron microscopy, non-contact atomic force microscopy, and scanning tunneling microscopy/spectroscopy. Linear I-V for bare silver nanowire suggests metallic behavior but high tunnel resistance indicates presence of insulating layer on the surface. Identical I-Vs obtained for isolated gold nanoparticle and heterostructure suggests that electron transport across nanowires in the latter is governed by gold nanoparticles in contrast to expected ballistic or diffusive transport along their length.(c) 2006 American Institute of Physics.

Electrochemical organization of monolayer protected gold nanoclusters on single-walled carbon nanotubes: significantly enhanced double layer capacitance - Mahima, Subhramanyam; Chaki, N. K.; Sharma, J.; Kakade, Bhalchandra A.; Pasricha, R.; Rao, A. M.; Vijayamohanan, K. (Journal of Nanoscience and Nanotechnology, 2006)
This paper reports a novel electrochemical route for anchoring monolayer protected gold nanoclusters (size 8 +/- 0.2 nm) on single-walled carbon nanotube bundles, resulting in the formation of hybrid materials. Monolayer protected gold nanoclusters prepared by modified Brust synthesis route were organized on SWNT bundles by cycling-the potential in dichloromethane between -1 to +1 V at a scan rate of 50 mV/s. Monolayer protected nanoclusters in electrolyte solutions possess ionic space charge around them (double layer charging), making them suitable for organization on nanotube bundles, by tuning the electrostatic interactions. More significantly, analysis of the double layer capacitance of these hybrid materials shows almost ten times increase in capacitance compared to that of bare SWNT bundles. We believe that these hybrid materials are potentially useful in nanoelectronics.
Keywords: double layer capacitance; double layer charging; hybrid materials; monolayer protected gold nanoclusters; single-walled carbon nanotubes